(untitled) (New York, NY, 2007)
Drawing on the current research base on the management of change, this book analyzes the key features in planning, delivery and monitoring the impact of planned change initiatives in higher education. Comparing and contrasting the findings of twenty-five action research high level corporate change management projects, the initiatives discussed include: the introduction of Kaplan and Norton’s "Balanced Scorecard" approach, resulting in strategic mapping at all levels; A major cultural shift programme to bring about globalisation of all aspects of the university, taking account the perspectives as to how this should be achieved; The introduction of a mentoring scheme to promote diversity and equality and greater understanding and support of black and ethnic minority staff.
Keywords: Universities and colleges,Educational leadership,Strategic planning,Education, higher; Administration,Administration; Great Britain,Great Britain,Great Britain,Great Britain